FEED BUNK HEIGHT IMPACT ON DAIRY COW'S FRONT CLAWS - CARVALHO, VICTOR CIACO DE; MOLLO NETO, MARIO; SOUZA, SILVIA REGINA LUCAS DE; VENTURI, PAOLO; NÄÄS, IRENILZA DE ALENCAR (Revista Brasileira de Engenharia de Biossistemas, 2009)
Claw horn lesions are believed to develop from increased pedal bone mobility induced by changes in the corium tissue. During the planning of barns herd owners are faced with choices of materials and dimensions, as well as feed bunk heights. Among the causes that may lead to front claw injuries there is the height of the feed bunk, as the cow changes its postural behavior in order to reach the food. This research aimed to study the dairy cows' front claws force exerted during eating for determining the lesion risk factor of the feed bunk height. Eight dairy cows were placed in front of the feed bunk, their front claws stepped on the pressure assessment system, and the forces exerted on front claws due to the eating postural change were recorded. The mean pressure, the maximum pressure, the floor contact area, and the mean force per region were calculated. While the cow was eating, the highest mean pressure shifted slightly towards the sole. In the lateral claw the maximum pressure was also shifted slightly towards the toe. No difference was found in the variables analyzed for both lateral and medial sides, as well for the force distribution in the left and right claws. Results of this experiment were not conclusive, not allowing explaining either laminitis or the corkscrew deformity as a result of the force exerted in the claws by means of height of the feed bunk being a risk factor.